Development of Low Cost Optical pH Sensor - Kazemzadeh, A.; Moztarzadeh, F. (Asian Journal of Chemistry, 2010)
A new low cost pH sensor was developed by immobilizing a direct indicator dye to porous and transparent acetylcellulose film. This sensor was fabricated by binding (Congo red and alizarin red S) to a cellulose acetate film that had previously been subjected to an exhaustive base hydrolysis for 24 h and increase the porosity of the membrane. The cellulose membranes were immediately treated with a mixture of 0.60% (w/v) thiourea and 0.50% (w/v) polyvinyl alcohol solution for 48 h at 25ºC. The cellulose membranes were separately treated with 0.1% (w/v) solution of alizarin red S at 35ºC and 0.050% (w/v) Congo red at 25ºC with magnetic stirring of the solution for 14 h. After washing, the films were dried at 45ºC for 20 min. Then the membranes had good durability (> 12 months) and a short response time (< 9 s). The method is easy to perform and uses acetylcellulose as a carrier. The reagents used for the activity of cellulose support are inexpensive, non-toxic and widely available.